Age, gender, and self-concept as predictors of solid waste management among residents in cross river state, Nigeria - Beshel, Cecilia Akpana; Asor, Love Joseph; Ojong, Aganyi Asu; Betiang, Peter Aniah; Ironbar, Virginia Emmanuel (International Journal of Management and Sustainability, 2024)
This research investigated the correlation between individuals’ age, attitude, and practices in handling solid waste in Cross River State, Nigeria. The study formulated three hypotheses to guide its direction and utilised a survey research design. The participants included 1,106 individuals selected through random sampling from a population of 6,923 using a stratified approach. The researchers developed a questionnaire, which six experts validated, and its reliability was assessed using Cronbach’s alpha method. Various statistical methods were employed to test the hypotheses at a significance level of 0.05, including simple regression, one-way analysis of variance (ANOVA), and an independent t-test. The outcomes revealed that age, gender, and self-concept influenced solid waste management practices within the studied population. Specifically, males and individuals with a strong self-concept exhibited more active engagement in solid waste management than their female and low-self-concept counterparts. The data indicated that respondents aged 38 and above demonstrated the highest level of involvement in solid waste management, followed by those aged 18-27. Conversely, respondents aged 28-37 exhibited the lowest extent of engagement in solid waste management practices. This study has valuable implications for policymakers, waste management professionals, and community stakeholders. The insights can guide the development of evidence-based strategies to encourage responsible waste management behaviours, thereby contributing to a cleaner and more sustainable future.